Finite element analysis of viscoelastic creep behaviors of deep-sea manned submersible viewport windows. (December 2020) - Liu, P.F.; Li, J.X.; Wang, S.B.; Leng, J.X.
Abstract: This paper studies the creep and damage behaviors of PMMA deep-sea manned submersible viewport windows under constant seawater pressure. First, the viscoelastic creep experiments of PMMA material specimens under four groups of tensile stresses (near 30 MPa) are performed. Second, we adopt the three-element spring/dashpot viscoelastic model to study the creep behaviors of the PMMA viewport windows without considering damage behaviors. Third, we develop a viscoelastic creep/damage coupled model to evaluate the creep behaviors of viewport windows by leveraging the Burgers viscoelastic model with four spring/dashpot elements. The main features are represented by three aspects: 1. the creep initiation, growth and acceleration stages are included, 2. the introduced damage variable into the creep model is featured by the void volume fraction, which represents the degradation of load-bearing ability of viewport windows and 3. the creep/damage coupling behaviors are reflected by the increased functional relationship between the damage variable and the equivalent strain. Fourth, the finite element algorithm using ABAQUS-UMAT (user material subroutine) is developed to implement the three-element and four-element spring/dashpot models, and the unknown viscoelastic parameters are identified by combining with the tensile creep experiments on PMMA material specimens. Finally, finite element analysis is performed to evaluate the distributions of the creep strain, displacement and damage variable of viewport windows by discussing the effects of the water depth (100–500 m and 3000 m). As an extreme case, the creep lifetime of the conical viewport window under 3000 m water depth is also evaluated from the conservative perspective. Highlights: A viscoelastic creep/damage coupled model is developed for creep analysis of PMMA viewport windows. Numerical algorithm using ABAQUS-UMAT subroutine is developed for creep models. Distributions of the creep strain, displacement and damage variable of viewport windows are discussed. Creep lifetime of the PMMA main conical viewport window under constant 3000m water depth is evaluated.